[18F]MK‐9470 PET measurement of cannabinoid CB1 receptor availability in chronic cannabis users. (27th December 2013) - Ceccarini, Jenny; Kuepper, Rebecca; Kemels, Dieter; van Os, Jim; Henquet, Cécile; Van Laere, Koen
Abstract Δ9‐Tetrahydrocannabinol, the main psychoactive component of cannabis, exerts its central effects through activation of the cerebral type 1 cannabinoid (CB1) receptor. Pre‐clinical studies have provided evidence that chronic cannabis exposure is linked to decreased CB1 receptor expression and this is thought to be a component underlying drug tolerance and dependence. In this study, we make first use of the selective high‐affinity positron emission tomography (PET) ligand [18F]MK‐9470 to obtain in vivo measurements of cerebral CB1 receptor availability in 10 chronic cannabis users (age = 26.0 ± 4.1 years). Each patient underwent [18F]MK‐9470 PET within the first week following the last cannabis consumption. A population of 10 age‐matched healthy subjects (age = 23.0 ± 2.9 years) was used as control group. Parametric modified standardized uptake value images, reflecting CB1 receptor availability, were calculated. Statistical parametric mapping and volume‐of‐interest (VOI) analyses of CB1 receptor availability were performed. Compared with controls, cannabis users showed a global decrease in CB1 receptor availability (−11.7 percent). VOI‐based analysis demonstrated that the CB1 receptor decrease was significant in the temporal lobe (−12.7 percent), anterior (−12.6 percent) and posterior cingulate cortex (−13.5 percent) and nucleus accumbens (−11.2 percent). Voxel‐based analysis confirmed this decrease and regional pattern in CB1 receptor availability in cannabis users. These findings revealed that chronic cannabis use may alter specific regional CB1 receptor expression through neuroadaptive changes in CB1 receptor availability, opening the way for the examination of specific CB1‐cannabis addiction interactions which may predict future cannabis‐related treatment outcome.